Holt physics - Serway; Faughn (Holt Rinehart & Winston Princeton, NJ, 2002)
This hardback Physics textbook is pre-owned but looks very good. It does have the name of previous owners in front of book. It also has been written pretty boy on the side of the pages as shown in the picture. I do not see any markings in the book unless I missed them. This is the student textbook.